Clarifying What Values? - Anderson, C. C. (Canadian Journal of Counselling and Psychotherapy, 2012)
Hague's (1977) theory of moral-conflict counselling for use by teachers, parents and counsellors, is criticized because of its excessive vagueness and the presence of thought cliches. Moreover, the authors on whom Hague relies for his information — Kohlberg, Dewey, Erikson — are themselves under siege. Implicit in Hague's theory is the hypothesis that effective counsellors must be at Kohlberg's most principled stages of moral reasoning. An empirical test was made of the extent to which this hypothetical situation could be implemented. From two studies of general samples of Education and Arts students to whom two test of values and the Eysenck Personality Inventory were administered, it was discovered that the Education students, most of whom are now teachers, were moderately deceitful and had the conventional tastes of the man in the street. It was concluded that, if these findings are representative, teachers will be unable to use Hague's moral-conflict therapy.